Diabetes-associated sustained activation of the transcription factor nuclear factor-κB - Bierhaus, Angelika; Schiekofer, Stephan; Schwaninger, Markus; Andrassy, Martin; Humpert, Per M.; Chen, Jiang; Hong, Mei; Luther, Thomas; Henle, Thomas; Klöting, Ingrid; Morcos, Michael; Hofmann, Marion; et al. (Diabetes, 2001)
Activation of the transcription factor nuclear factor-κB (NF-κB) has been suggested to participate in chronic disorders, such as diabetes and its complications. In contrast to the short and transient activation of NF-κB in vitro, we observed a long-lasting sustained activation of NF-κB in the absence of decreased IκBα in mononuclear cells from patients with type 1 diabetes. This was associated with increased transcription of NF-κBp65. A comparable increase in NF-κBp65 antigen and mRNA was also observed in vascular endothelial cells of diabetic rats. As a mechanism, we propose that binding of ligands such as advanced glycosylation end products (AGEs), members of the S100 family, or amyloid-β peptide (Aβ) to the transmembrane receptor for AGE (RAGE) results in protein synthesis-dependent sustained activation of NF-κB both in vitro and in vivo. Infusion of AGE-albumin into mice bearing a β-globin reporter transgene under control of NF-κB also resulted in prolonged expression of the reporter transgene. In vitro studies showed that RAGE-expressing cells induced sustained translocation of NF-κB (p50/p65) from the cytoplasm into the nucleus for >1 week. Sustained NF-κB activation by ligands of RAGE was mediated by initial degradation of IκB proteins followed by new synthesis of NF-κBp65 mRNA and protein in the presence of newly synthesized IκBα and IκBβ. These data demonstrate that ligands of RAGE can induce sustained activation of NF-κB as a result of increased levels of de novo synthesized NF-κBp65 overriding endogenous negative feedback mechanisms and thus might contribute to the persistent NF-κB activation observed in hyperglycemia and possibly other chronic diseases.